Optimizing Family Law Counseling Through Social Media to Create a Legally Intelligent Society - Nur Putri Hidayah; Komariah Komariah; Ahmad Dzaki Abidin; Torri Justiansyah; Aldi Malik Farhad; Karina Ghea Silvana; Ordelia Julayta Syahidah (Universitas Negeri Semarang, 2023)
Social media is currently used optimally by the public as a means of sharing information. No exception in terms of providing massive education. In the realm of law, increased education can be done through legal counselling. Increasing education is important because various studies have proven that high legal literacy can prevent legal problems, especially family law. Family law issues themselves are an issue in society, as evidenced by the high divorce rate in various religious courts, including the Religious Courts of Malang City and Malang Regency. Together with LBH Peradi Malang Raya, the servant optimizes legal counseling through Instagram and Tiktok social media, targeting Instagram and Tiktok user communities in Malang City, Batu City and Malang Regency. Servants compiled 9 (nine) legal educational videos with the theme of family law. Public enthusiasm is quite high in this video with a total of 33,035 views, 2,212 likes, and 169 comments.